A retrospective study of colorectal cancer CT imaging features involving microsatellite instability - Stearns, Jack; Chiu, Albert; Hutzley, Samantha; Kuckelman, Tristan; Kloft, Luke; Bay, Curt; Kundranda, Madappa N.; Chang, John (Journal of clinical oncology, 2025)
265Background: This study aimed to identify correlations between CT imaging characteristics accessible to the radiologist with microsatellite instability (MSI) status among colorectal cancer. Noninvasive identification of MSI status can decrease time to treatment if pathology can be bypassed. Methods: 109 colorectal cancer patients were identified retrospectively from 2011 to 2018 with an average age of 61 years (58 male, 51 female) and had MSI pathological assessment. These subjects all had CT abdomen and pelvis obtained at the time of initial diagnosis. Imaging features of both the primary and metastatic lesions were assessed. Primary lesion features included: location, size, stage, attenuation compared to the liver, growth pattern, tumor margin, primary mass area, and the presence/absence of mesenteric infiltration. Metastatic lesion features included: size, attenuation relative to liver, and enhancement pattern. Patient age, sex, and tumor staging were obtained from patient medical records. Statistical analysis was performed using various methods, including chi-square, Mann-Whitney and Kruskal-Wallis tests. Results: 5 tumor characteristics displayed a statistically significant relationship with MSI status. MSI-H lesions were more likely to be clinical Stage 2, and MSI-L lesions were more likely to be Clinical Stage 3 (p=0.012). Tumors with distant metastasis were more likely MSI-L versus regional metastasis were more likely MSI-H (p<0.001). Primary mass area was larger in the MSI-H than MSI-L group (p<0.001). Tumors in the left colon are more likely to be MSI-L versus CRC tumors in the right colon are more likely to be MSI-H (p<0.001). MSI-H tumors had a lower primary tumor Hounsfield Unit standard deviation (SD) than MSI-L tumors (p=0.002). The remaining features were not statistically significant. For primary lesion, these include mesenteric infiltration (p=0.189), tumor margin (p=1.000), enhancement pattern (p=0.498), growth pattern (p=0.127), tumor CT density (p=0.162), and liver density (p=0.105). Enhancement of metastasis also had no difference (p=0.376). Conclusions: Multiple CT imaging characteristics were predictive of MSI classification in CRC tumors, holding potential clinical relevance that can help guide individualized therapy. While these results were statistically significant, more research must be done to validate these findings and to derive useful nomograms.